Avaliação do perfil microbiano intestinal em ratos Wistar diabéticos tipo 1 tratados com diferentes doses de Resveratrol - Adami, Bruno Silveira (2016)
The number on the citations of resveratrol has been increased over the last decade. This increase is directly related to the versatility of compound, commonly known by the benefits of wine. Contiguous to resveratrol, another growing issue in the scientific community is the microbiota and its possible modulation by compounds with prebiotic action. It is well know that resveratrol does not have a consolidated mechanism of action, and large amounts of the compound are retained in the gastrointestinal tract, we analyze the influence of resveratrol ingestion and their metabolite in populations of specific bacteria. For the induction of intestinal dysbiosis, we used experimental model of type 1 diabetes in rats. The treatment with resveratrol was performed during thirty days with daily doses of 5, 10 and 20 mg.kg-1. The quantification of the metabolite and resveratrol was accomplished through UPLC-MS/MS (Ultra-Performance Liquid Chromatography-Electrospray Tandem Mass Spectrometry). Quantification of A. muciniphila, Bacteroidetes and Prevotella was carried out by qPCR (Polymerase Chain Reaction). The study demonstrated increased population of A. muciniphila, Bacteroidetes and Prevotella in both normal and diabetic rats trated with resveratrol. This increase presented nonlinear response. The metabolite production was dose-dependent, however, a significant increase was observed in healthy animals compared to diabetic rats. We also observed significantIt is also observed correlation between different bacteria and resveratrol metabolite in healthy and diabetic animals. In conclusion, our study show that treatment with resveratrol promote changes in the microbiota. Data also reveled an increase in bacterial populations very important for intestinal health, such as: A. muciniphila, Bacteroidetes in healthy and diabetic Wistar rats in nonlinear manner.